2021
DOI: 10.1021/acssensors.1c00051
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Nitric Oxide in Cells: Historical Technologies and Future Outlook

Abstract: Nitric oxide (NO) is a critical cell signaling molecule with important roles in both normal cellular physiology and pathology. Over the past 20 years, multiple sensing modalities have been developed for the intracellular synthesis (endogenous) and release (exogenous) of NO. In this review, we survey the historical progression of NO sensing platforms, highlight the current state of the art, and offer a forward-looking view of how we expect the field of NO sensing to develop in the context of recent advances in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…However, real-time analysis of NO is challenging due to its unique molecular properties in biological systems, including fast diffusion (diffusion constant 3300 μm/s 2 ), small size, and hydrophobicity (XlogP: 0.2). , Current methods are mainly developed for the indirect analysis of NO, such as high-performance liquid chromatography (HPLC), electron paramagnetic resonance (EPR), chemiluminescence, and fluorescence detection techniques . These methods have been used in many studies but are limited by the complexity of sophisticated instruments and additional chemical reagents.…”
Section: Introductionmentioning
confidence: 99%
“…However, real-time analysis of NO is challenging due to its unique molecular properties in biological systems, including fast diffusion (diffusion constant 3300 μm/s 2 ), small size, and hydrophobicity (XlogP: 0.2). , Current methods are mainly developed for the indirect analysis of NO, such as high-performance liquid chromatography (HPLC), electron paramagnetic resonance (EPR), chemiluminescence, and fluorescence detection techniques . These methods have been used in many studies but are limited by the complexity of sophisticated instruments and additional chemical reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, mass spectrometry (MS) is increasingly emerging as a powerful tool for identifying and quantifying various classes of metabolites from complex biological samples at high coverage, sensitivity, and specificity. Despite its powerful capabilities, direct MS detection of NO is impossible since NO is highly diffusible, unstable, and a gaseous free radical. In the past decades, widespread interest in NO and its biological roles has prompted the developments of various analytical techniques capable of its measurement and quantification, such as colorimetry, electrochemical sensors, and fluorescence techniques. Generally, these methods only measure one specific analyte and indeed show high specificity and sensitivity. However, multiplexing assay via these techniques is an extremely hard task. , To address this problem, a straightforward approach is hyphenated to high-throughput methods such as MS. For instance, Zhao et al have reported a novel approach by combining electrochemistry and high-resolution MS (HRMS), in which electrochemistry is applied for in situ detection of NO release, while HRMS can be used for metabolite profiling in breast cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…Among many detection methods reported, fluorescence imaging occupies a very advantageous position in the detection of biological species due to its superiority of convenient use, noninvasive detection, real-time visualization, and low cost. , So far, a number of fluorescent probes have been developed for the detection of NO. , These probes are basically constructed by linking a fluorophore at a certain optical window to a recognition moiety, which specifically reacts with NO under physiological conditions. The reported reactions include o -phenylenediamine (OPD) cyclization, dihydropyridine (DHP) oxidation, metal coordination, etc. However, the inherent defects of these reactions with NO have greatly limited the biological applications of these probes. For example, fluorescent probes based on OPD and DHP can be oxidized by biologically active species like ascorbic acid (AA), dehydroascorbic acid (DHA), and methylglyoxal (MGO) and produce false positive signals .…”
mentioning
confidence: 99%